Phytoplankton Growth and Productivity in the Western North Atlantic: Observations of Regional Variability From the NAAMES Field Campaigns - Fox, James; Behrenfeld, Michael J.; Haëntjens, Nils; Chase, Alison; Kramer, Sasha J.; Boss, Emmanuel; Karp-Boss, Lee; Fisher, Nerissa L.; Penta, W. Bryce; Westberry, Toby K.; Halsey, Kimberly H. (Frontiers in Marine Science, 2020)
The ability to quantify and explain spatial and temporal variability in phytoplankton growth and productivity is essential to improving our understanding of global carbon dynamics and trophic energy flow. Satellite-based observations offered the first opportunity to estimate depth-integrated net primary production (NPP) at a global scale, but early modeling approaches could not effectively address variability in algal physiology, particularly the effects of photoacclimation on changes in cellular chlorophyll. Here, a previously developed photoacclimation model was used to derive depth-resolved estimates of phytoplankton division rate (µ) and NPP. This approach is in strong agreement with discrete measurements of 14C-based NPP (r2 = 0.80) and effectively captured both spatial and temporal variability observed during four field expeditions of the North Atlantic Aerosols and Marine Ecosystems Study (NAAMES). We observed favorable growth conditions for phytoplankton throughout the annual cycle in the subtropical western North Atlantic. As a result, high rates of µ are sustained year-round resulting in a strong coupling between growth and loss processes and a more moderate spring bloom compared to the high-latitude subarctic region. Considerable light limitation was observed in the subarctic province during the winter, which resulted in divergent growth dynamics, stronger decoupling from grazing pressure and a taxonomically distinct phytoplankton community. To further our understanding of global carbon cycling, more detailed knowledge of the spatial and temporal dynamics of phytoplankton division rate is required, not only to provide insight into the resulting influence on phytoplankton taxonomy, but also the loss processes that dictate the fate of fixed carbon.